Thoracoscopic left cardiac sympathetic denervation in a child with refractory long QT syndrome - Sachit Anand; Vishesh Jain; Sandeep Agarwala; Sakshi Sachdeva; Shyam Sunder Kothari (Wolters Kluwer Medknow Publications, 2019)
Long QT syndrome is a cardiac disorder which presents with recurrent syncopal attacks and has risk of sudden cardiac death. A 5-year-old boy presented to us with this syndrome. The child was symptomatic despite medical management and was successfully managed with cardiac denervation. The current report highlights the efficacy and safety of the use of video-assisted thoracoscopic surgery for this procedure.